The Effectiveness of the Phase II Cardiac Rehabilitation Program on the Functional Capacity of the Heart and Quality of Life of Post-CABG Patients - Deddy Wandra Maraksa; Nur Asnah Sitohang; Mula Tarigan (GLOBAL HEALTH SCIENCE GROUP, 2025)
The Coronary Artery Bypass Graft (CABG) procedure is a form of surgical intervention carried out to treat coronary heart disease (CHD). Cardiac rehabilitation programs are training and education programs that aim to improve patients' heart health, especially after surgery. One of the goals of cardiac rehabilitation is to return patients to achieve optimal conditions, increase the functional capacity of the heart, and improve the quality of life. The purpose of the study was to test the effectiveness of the phase II cardiac rehabilitation program on increasing cardiac functional capacity and quality of life of post-CABG patients at H. Adam Malik Hospital Medan. The research design is a quasi-experimental one group pre-test and post-test design. The sampling technique is purposive sampling. The number of samples was 33 respondents. Data analysis was conducted using dependent t tests for heart rate (HR), systolic blood pressure, and diastole blood pressure. Data on respiratory rate (RR), METs, oxygen saturation (SpO2), and quality of life variables were used to test the wilcoxon. The results of the data analysis showed that there was no effect of the phase II cardiac rehabilitation program on HR and RR (p>0.05 value) because the majority of respondents took beta-blocker drugs. However, the results of statistical tests showed that there was an effect of the phase II cardiac rehabilitation program on systole and diastole blood pressure, METs, SpO2, and the quality of life of the respondents (p value <0.05). This study proves that the phase II cardiac rehabilitation program is effective in improving the functional capacity of the heart and the quality of life of post-CABG patients.